ISLAMIC EDUCATION POLICY ROADMAP IN THE ERA OF DIGITAL DISRUPTION: A SYSTEMATIC LITERATURE - Puspitasari, Ria; Rodiyah, Sinta; Arrauf, Ziddan; Amalia, Tin; Junaidah, Junaidah; Amiruddin, Amiruddin (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to analyze the direction and form of the Islamic education policy roadmap in the era of digital disruption, with a focus on technology integration and strengthening digital ethics based on Islamic values. The method used was a Systematic Literature Review with the PRISMA 2020 protocol and the JBI framework, reviewing national and international literature from SINTA 2 and 3 journals over the past five years. The results indicate that Islamic education policies, digitalization strategies, and curricula face challenges such as infrastructure readiness, teacher capacity, and suboptimal values-based governance and evaluation. An effective integration model combines digital innovation, value-based design, and ethical governance that maintains moral-pedagogical aspects. Implementation of digital ethics that emphasizes the principles of trust, etiquette, responsibility, and privacy protection in the curriculum, training, and regulations. The research recommends that an adaptive and values-based policy roadmap with pillars of ethics-by-design, adaptive governance, and community co-production for moral, contextual, and sustainable policies.